2010
DOI: 10.2527/jas.2009-2541
|View full text |Cite
|
Sign up to set email alerts
|

Growth characteristics, reproductive performance, and evaluation of their associative relationships in Brangus cattle managed in a Chihuahuan Desert production system1

Abstract: Balancing growth and reproductive performance in beef cattle managed in desert environments is challenging. Our objectives were to 1) evaluate trends in growth and reproductive traits, and 2) assess associative relationships between growth characteristics and reproductive performance in a Brangus herd managed in a Chihuahuan Desert production system from 1972 to 2006. Data were from bull (n = 597) and heifer calves (n = 585; 1988 to 2006) and cows (n = 525; repeated records of cows, n = 2,611; 1972 to 2006). V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Changes in the gene expression of ADIPOQ and its receptors were associated with ovarian follicular recruitment and luteal function in Holstein cows [56]. Cumulatively, these results provide gene-specific information to support the rationale for long-term study of the relationships of adiposity with fertility in Brangus cattle [57], [48], [58].…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Changes in the gene expression of ADIPOQ and its receptors were associated with ovarian follicular recruitment and luteal function in Holstein cows [56]. Cumulatively, these results provide gene-specific information to support the rationale for long-term study of the relationships of adiposity with fertility in Brangus cattle [57], [48], [58].…”
Section: Resultsmentioning
confidence: 80%
“…Eight Brangus (3/8 Brahman x 5/8 Angus) heifers representing the pedigree diversity observed in GWAS of fertility traits were selected for this study from the New Mexico State University Brangus breeding program [11], [18], [19], [58]. Averages for fertility trait measures indicative of early puberty in this study were: ACL (651 days), FSC (53.3%), and HPG (78.0%)[10], [11], [19], [58].…”
Section: Methodsmentioning
confidence: 99%
“…Regions responsible for the expression of reproductive traits (quantitative trait loci, QTLs) such ovulation and twinning rate have been identified on this chromosome [30, 31, 32, 33]. Daetwyler et al [30] and Cruickshank et al [34] found that the window of 45 to 50 Mb on BTA5 is associated with AFC and twinning rate in cattle.…”
Section: Resultsmentioning
confidence: 99%
“…The positive associations between AFC and weight gain from birth to weaning and between AFC and conformation at weaning may also be explained by the fact that weight gain is genetically determined and associated to mature size. Selection for weaning and yearling weights of replacement heifers result in cows with bigger mature sizes (Klosterman, 1972), which may negatively affect female fertility (Luna-Nevarez et al, 2010).…”
Section: Discussionmentioning
confidence: 99%